2023
DOI: 10.3390/ijerph20065068
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study to Assess a Systematic Screening of Occupational Exposures in Lung Cancer Patients

Abstract: Occupational lung cancer cases remain largely under-reported and under-compensated worldwide. In order to improve the detection and compensation of work-related lung cancers, we implemented a systematic screening of occupational exposures, combining a validated self-administered questionnaire to assess occupational exposures and a specialized occupational cancer consultation. After a pilot study, the present prospective, open-label, scale-up study aimed to assess this systematic screening of occupational expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This monocentric study was conducted at the Center Léon Berard (CLB), a comprehensive cancer center in Lyon, France, affiliated with the National Federation of Cancer Centers Unicancer ( 10 ). Patients included in the study had histologically confirmed lung cancer, were treated at the CLB, and were prospectively integrated in the PROPOUMON ( 11 , 12 ) database between March 25, 2014 and August 31, 2020. Non-inclusion criteria were residence outside the Auvergne-Rhône-Alpes region, unknown addresses, missing data for the covariates, and refusal to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…This monocentric study was conducted at the Center Léon Berard (CLB), a comprehensive cancer center in Lyon, France, affiliated with the National Federation of Cancer Centers Unicancer ( 10 ). Patients included in the study had histologically confirmed lung cancer, were treated at the CLB, and were prospectively integrated in the PROPOUMON ( 11 , 12 ) database between March 25, 2014 and August 31, 2020. Non-inclusion criteria were residence outside the Auvergne-Rhône-Alpes region, unknown addresses, missing data for the covariates, and refusal to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…To improve detection of occupational cancers and their compensation, a systematic screening of occupational exposures, combining a self-administered questionnaire and specialized occupational cancer consultation has been implemented since 2009, in collaboration with the Lyon University occupational health services. We have demonstrated that this systematic screening and outreach process can improve compensation for occupational lung cancer and that it can be used in other comprehensive cancer centers ( 17 ).…”
Section: Contextmentioning
confidence: 99%
“…Of these, 176 were selected following the responses for a specialist consultation. Only 150 people showed up for this consultation and 88 of them (7% of the initial number of participants) were diagnosed with occupational lung cancer [11]. Screening questionnaires are applied, in general, to reduce the number of exposure-workers within a target group to then carry out radiological/ low dose chest CT screening.…”
Section: Screeningmentioning
confidence: 99%